FROM BYTES TO BILLIONS: A COMPREHENSIVE UNDERSTANDING OF VALUE STREAMS IN THE DIGITAL ECONOMY - Loso Judijanto; Tri Apriyono; Devi Trenggani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The digital economy has changed the way value is built and distributed around the world. In this context, data is no longer just a collection of information, but rather a key source of economic value that can be processed into innovative business insights and solutions. This study highlights how raw data, in the form of bytes, can be transformed into billions of dollars through various analytics technologies and processes. In addition, the research explores the role of cutting-edge technologies, such as artificial intelligence and blockchain, as well as policies that support innovation and effective data protection. Human factors also take centre stage, with an emphasis on the importance of digital skills development as well as cross-sector collaboration to build an ecosystem that supports inclusive growth. The findings offer a comprehensive perspective on value streams in the digital economy, as well as strategic recommendations to maximise the potential that exists in this digital age.